The Hague Service Convention 1965: Is it Shari‘ah Compliant? - Kamaruddin, Zaleha; Eishan Jan, Mohammad Naqib (INSI Publications, 2012)
The issue of amenability of an international treaty, like the ‘Hague Service Convention 1965’, with the Shari’ah is crucial from a Muslim state perspective and it has to be settled before the State in question can ratify the treaty and thereby expressing her willingness to abide by its provisions. This is crucial in the sense that once a treaty is ratified and come into force the treaty shall be binding upon its contracting states under both contemporary international law and the Shari‘ah. Muslim States or for that matter any other state, do not want to obligate themselves by a treaty that adversely affects their religious beliefs, national laws or sovereignty. In this paper attempt is made to determine whether the Hague Service Convention 1965 is Shari‘ah compliant. In determining this it is important to studythe Convention’s objectives for if its objectives are align with the higher ideals and objectives of Shari‘ah (Maqasid al-Shari‘ah) then the treaty in question,which calls for judicial cooperation among its members, can securely be adopted by Muslim states without affecting their substantive laws or sovereignty.